Public provision of private goods and nondistortionary marginal tax rates - Sören Blomquist; Vidar Christiansen; Luca Micheletto (Center for Economic Studies and ifo Institute (CESifo), 2008)
The incidence and efficiency losses of taxes have usually been analysed in isolation from public expenditures. This negligence of the expenditure side may imply a serious misperception of the effects of marginal tax rates. The reason is that part of the marginal tax may in fact be payment for publicly provided goods and reflects a cost that the consumers should bear in order to face the proper incentives. Hence, part of the marginal tax serves the same role as a market price in the sense that it conveys information about a real social cost of working more hours. We develop this idea formally by studying an optimal income tax model in combination with a type of public provision scheme not analyzed before; the provision level is individualized and positively associated with the individual's labor supply. As examples we discuss child care, elderly care, primary education and health care. We show that there is a gain in efficiency where public provision of such a service replaces market purchases. We also show that it is necessary for efficiency that marginal income tax rates are higher than in economies where the services are purchased in the market. This is because the optimal tax should be designed so as to face the taxpayers with the real cost of providing the services. Hence, it might very well be that economies with higher marginal tax rates have less severe distortions than economies with lower marginal tax rates.
Keywords: H21; H42; I38; 330; nonlinear income taxation; marginal income tax rates; public provision of private goods; in-kind transfers; Einkommensteuer; Grenzsteuersatz; Öffentliche Dienstleistung; Wohlfahrtseffekt; Optimale Besteuerung; Sachtransfer; Theorie